NEWCOMERS’ SOCIALIZATION: THE PROACTIVE BEHAVIORS, SATISFACTION AND SOCIAL INTEGRATION - James, R.; Kowsikka, F.M.J.J. (University of Jaffna, 2019)
When newcomers enter into organizations they often feel stressed and find difficulties to adjust to the new organizational context. Through the socialization process they learn how to adjust to the new context. Previous studies investigated the role of organizations in the process of newcomer adjustment. However, the individual role in newcomer adjustment has not been sufficiently discussed in the literature; particularly there is no such study in the Sri Lankan context. This study examines the influence of newcomer proactive behaviors (positive framing, relationship building, information seeking and feedback seeking) on adjustment (job satisfaction and social integration). This study was conducted with 114 newcomers who had less than one year of work experience from banking sector in Northern Province of Sri Lanka. The study employed PLS-SEM with Smart PLS to test the proposed hypotheses. The findings revealed that among the four proactive behaviors, positive framing positively influences both satisfaction and social integration. Information seeking, feedback seeking and relationship building also positively influence either job satisfaction or social integration. These findings suggest that newcomers need to engage in proactive behaviors to achieve satisfaction at the workplace and to become acceptable members of the organization. Further, this study contributes to the literature by investigating the influence of proactive behavior in the socialization process among new employees in the banking sector in the Sri Lankan cultural context.
Keywords: job satisfaction; social integration; proactive behavior; adjustment; organizational socialization